(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The Australian Defence Force English Language Profiling System (ADFELPS) is an English language proficiency rating system used to assess the English language skills of Malaysian candidates and to describe the levels of English required for target courses conducted by the Australian Defence Forces (ADF) and the New Zealand Defence Forces (NZDF). It covers all the four language skills i.e. Reading, Writing, Listening and Speaking and it is graded from Level 1 to a maximum of Level 9 which is a native speakers proficiency. Currently, Malaysian officers have some difficulty getting a Level 7 and above for the ADFELPS Writing Scale. Although there are some officers who are at Level 7 or Level 8 at the other language skills, they have difficulty going from Level 6 to Level 7 for the Writing skill. An English language writing workshop was held at the Armed Forces Library over three days to improve the writing skills of Malaysian Armed Forces (MAF) Officers. The main aim of this course was to improve the writing skills for MAF officers especially for officers who are going for overseas courses where the minimum ADFELPS level is a Level 6. The course covered grammar, coherent and cohesive writing, analyzing a typical five paragraph essay, culminating in the students being given two essays and being graded at ADFELPS writing scales. The results show that there has been a deterioration of writing skills of MAF officers and some of the problems related to writing will be discussed in this paper.